2021
DOI: 10.1007/s00784-021-04079-0
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective fractal analyses of one-year follow-up data obtained after single-visit nonsurgical endodontic retreatment on periapical radiographs

Abstract: ObjectivesThe aim of retrospective study was to evaluate the changes to the periapical bone sites after non-surgical endodontic retreatment by using fractal analysis on periapical radiographs. Materials and methods Thirty patients whose teeth had periapical lesions and underwent primary endodontic treatment were selected for nonsurgical single-visit endodontic retreatment. Two radiographs were taken, the first immediately after retreatment and the second at the 1-year follow-up. An identical region of interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…It has been reported that the FD value calculated by the studies is not affected by variables such as irradiation time (mAs), kilovolt peak acceleration voltage (kVp), and projection angle, therefore fractal analysis can be performed with non-standardized radiographs during the filming of (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the FD value calculated by the studies is not affected by variables such as irradiation time (mAs), kilovolt peak acceleration voltage (kVp), and projection angle, therefore fractal analysis can be performed with non-standardized radiographs during the filming of (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…According to the PAI system, which is the commonly used index in the literature in the analysis of radiographic findings, PAI 1 and 2 scores are reported as healing in most of the studies. 8,[15][16][17] In this study, the same scores were taken as a reference. A healing pattern (PAI 1 and PAI 2 scores) was observed at the end of 1 year in all 29 teeth included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…3.1.9.2, Franz Faul; Universitat Kiel, Germany), a total sample size of 29 is required when α = 0.05, and the effect size is 0.45, which would yield a power of 0.80. 15 Periapical radiographs (T0) and 1-year follow-up radiographs (T1) taken immediately after retreatment of 29 individuals who were admitted to the endodontic clinic between 2020 and 2021 with indications for retreatment were used.…”
Section: Sample Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teeth with previously endodontic treatment but unsuccessful and developing AP, root canal obturation 2 mm shorter than the working length and teeth that do not show adequate obturation, Patient with systemic disorders related to bone metabolism and using drugs that may affect bone metabolism, Patient with acute pain and therefore using analgesic medication in the last 24 hours, Patient with using antibiotics 2 weeks before the treatment, Patients who could not attend control sessions were excluded from the study [13].…”
Section: Inclusion Criteriamentioning
confidence: 99%